Exploring the in vitro effects of Helichrysum petiolares for its potential to provide cardioprotective benefits against Doxorubicin toxicity - Bredenkamp, Jhade Cameron (Stellenbosch : Stellenbosch University, 2026)
Thesis (MSc)--Stellenbosch University, 2026.